Effects of different doses of nandrolone decanoate on estrous cycle and ovarian tissue of rats after treatment and recovery periods - Simão, Vinícius Augusto [UNESP]; Berloffa Belardin, Larissa [UNESP]; Araújo Leite, Gabriel Adan [UNESP]; de Almeida Chuffa, Luiz Gustavo [UNESP]; Camargo, Isabel Cristina Cherici [UNESP] (Wiley, 2015)
This study tested the hypothesis that different doses of nandrolone decanoate (ND) will cause changes in the estrous cycle and ovarian tissue of adult rats; and investigated the duration of the recovery period that is sufficient to restore the damage in the animals treated with different doses. Wistar rats were treated with ND at doses of 1.87, 3.75, 7.5 and 15 mg/kg body weight, or received mineral oil (control group) for 15 days, subcutaneously. All animals were divided into three groups according to the treatment periods: (i) ND treatment for 15 days; (ii) ND treatment followed by a 30-day recovery; and (iii) ND treatment followed by a 60-day recovery. Estrous cycle was monitored daily, and at the end of each period, the animals were euthanized for histopathological analysis. During ND treatment and after 30-day recovery, all animals exhibited persistent diestrus. After a 60-day recovery, persistent diestrus was only maintained in the group that had received the highest dose. Ovarian weight was decreased significantly after the 30-day recovery, regardless of ND doses, compared with the control group. There was a reduction (P < 0.05) in the number of corpora lutea and antral and growing follicles, in contrast to an increase (P < 0.05) in atretic follicles in a dose- and time-dependent manner. Remarkable histopathological changes occurred in the ovaries of all ND-treated groups. In conclusion, the different doses of ND caused changes in the estrous cycle and ovarian tissue of rats, and recovery periods (30 and 60 days) were insufficient to completely restore the damage in the animals treated with the highest dose.
Keywords: Estrous cycle; Nandrolone decanoate; Ovarian histopathology; Rats; Recovery period